Effects of nucleus initialization on event-by-event observables - Tavares,B. Mattos (2007)
In this work we present a study of the influence of nucleus initializations on the event-by-event elliptic flow coefficient, v2. In most Monte-Carlo models, the initial positions of the nucleons in a nucleus are completely uncorrelated, which can lead to very high density regions. In a simple, yet more realistic model where overlapping of the nucleons is avoided, fluctuations in the initial conditions are reduced. However, v2 distributions are not very sensitive to the initialization choice.